Serum level of TNF-α, IL-1 and IL-6 and serum biomarkers after nutritional change in patients’ ventilator-associated pneumonia: serum biomarkers in ventilator-associated pneumonia - Lu, Peng (Journal of Medical Biochemistry, 2025)
Objective: The research targets to explore the clinical research of high-protein nutritional support combined with probiotics (Bifid Triple Live Bacteria Capsules) to improve critically ill patients’ nutritional conditions and prevent ventilator-associated pneumonia and clinical value of TNF-α, IL-1 and IL-6 and serum biomarkers. Methods: 86 critically ill patients requiring continuous ventilator support in the ICU department of the central hospital from March 2023 to December 2024 are recruited as study objects. Patients are randomly broken into the research group (n=46) or the control group (n=40). Both groups are given enteral nutrition emulsion TPF (Rexen), and whey protein powder is given nutritional support according to the total protein intake standard of 1.5 2.0g/kcal/d. On the basis of the control group, the research group receive individualized high-protein nutritional support, supplemented by probiotics (bifidobacteria triple live capsule) intervention. The study period is 3 weeks. The clinical data of the two groups are statistically compared. The patients’ body mass index (BMI) and body weight are calculated and compared. The content of serum protein is measured by spectrophotometer. The prevalence of ventilator-associated pneumonia is analyzed by sputum gram staining. The clinical symptoms of patients with ventilator-associated pneumonia during ICU are monitored. Serum levels of inflammatory cytokines TNF-α, IL-1 and IL-6 are detected by ELISA. Results: There was no difference in general data between the two groups (P>0.05). The body weight and BMI of the patients in the research group were higher than those in the control group (P<0.05). The content of serum albumin, serum prealbumin and the ratio of serum albumin/total protein in the research group were higher than those in the control group (P<0.05). The infection rate of ventilator-associated pneumonia in the control group was higher than that in the research group (P<0.05). The incidence of clinical symptoms of ventilator-associated pneumonia in the research group was lower than that in the control group (P<0.05). The levels of serum TNF-α, IL-1 and IL-6 in the research group were lower than those in the control group (P<0.05). Conclusion: High-protein nutritional support combined with probiotics can significantly raise the nutritional conditions of critically ill patients, and can effectively prevent the occurrence of ventilator-associated pneumonia. This intervention may play a role by promoting the nutritional level of patients and regulating the inflammatory response, and has potential clinical application value in the management of critically ill patients in ICU.